2010
DOI: 10.1186/1471-2148-10-114
|View full text |Cite
|
Sign up to set email alerts
|

Non-random genomic integration - an intrinsic property of retrogenes in Drosophila?

Abstract: BackgroundThe Drosophila X-chromosome shows a significant underrepresentation of genes with male-biased gene expression (demasculinization). This trend is matched by retrogenes, which typically have a male biased gene expression pattern and show a significant movement bias from X-chromosomes to autosomes. It is currently assumed that these patterns are best explained by selection, either mediated by male meiotic sex chromosome inactivation (MSCI) or sexually antagonistic forces. We scrutinized the evolutionary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(61 citation statements)
references
References 36 publications
(39 reference statements)
1
59
0
1
Order By: Relevance
“…However, a recent study indicates that retroposing genes with diverse expression biases all show an affinity toward autosomes [15]; therefore the apparent 'exodus' of male-biased genes from the X , previously considered as the major indirect evidence for MSCI in flies [1], is not necessarily driven by sexual selection. Earlier studies did show that not only testis-biased, but also somatic male-biased genes are underrepresented on the X [42], but the possible role of these genes in sexual selection could still be invoked with certain ease owing to their sex bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study indicates that retroposing genes with diverse expression biases all show an affinity toward autosomes [15]; therefore the apparent 'exodus' of male-biased genes from the X , previously considered as the major indirect evidence for MSCI in flies [1], is not necessarily driven by sexual selection. Earlier studies did show that not only testis-biased, but also somatic male-biased genes are underrepresented on the X [42], but the possible role of these genes in sexual selection could still be invoked with certain ease owing to their sex bias.…”
Section: Discussionmentioning
confidence: 99%
“…Two main explanations have been given for the excess of retrotransposition involving the X chromosome: escape from meiotic sex chromosome inactivation (Betrán et al 2002;Vibranovski et al 2009a) and sexually antagonistic selection against male-favorable genes (Ranz et al 2003;Wu and Xu 2003;Vicoso and Charlesworth 2006). In addition, nonadaptive explanations-such as biased integration of reverse-transcribed cDNAs onto autosomes (Metta and Schlotterer 2010)-have been put forward, though studies of the movement of pseudogenized retrogenes in both Drosophila and mammals have not found any biased integration (Emerson et al 2004;Potrzebowski et al 2008;Meisel 2009), nor has such a bias been observed with respect to transposable elements (Fontanillas et al 2007). Much of the evidence for selection driving retrogenes off the X has been correlative: Such retrogenes often have testis-biased or even testis-specific gene expression, a pattern consistent with the advantage of autosomal copies that are not precociously silenced during spermatogenesis (Betrán et al 2002;Vibranovski et al 2009a).…”
mentioning
confidence: 99%
“…The recent study by Metta and Schlötterer [21] proposed a new interpretation which negated the need for selection-based hypotheses to understand the out-of-the X movement pattern of Drosophila retrogenes. To test the general role of natural selection, Metta and Schlötterer [21] identified retrogenes for which the parental gene has been lost or degenerated.…”
Section: Introductionmentioning
confidence: 99%
“…To test the general role of natural selection, Metta and Schlötterer [21] identified retrogenes for which the parental gene has been lost or degenerated. In other words, the parental genes and retrogenes are never found in the same species.…”
Section: Introductionmentioning
confidence: 99%